The Role of Motivation, Leadership, and Communication in Enhancing Employee Performance at the Buleleng Regency Tourism Office as a driver of the local economy - Saisarani, Kadek Gita Puspita; Rahmawati, Putu Indah; Telagawathi, Ni Luh Wayan Sayang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of work motivation, leadership, and communication style—both individually and collectively—on employee performance at the Buleleng Regency Tourism Office. This research employed a population study design, involving all 42 employees with the status of State Civil Apparatus at the office. Data were collected using a survey method with a structured questionnaire as the research instrument. The data were analyzed using multiple linear regression with the assistance of SPSS 21 for Windows. Prior to hypothesis testing, data quality assessments and classical assumption tests were conducted, including tests for normality, multicollinearity, and heteroscedasticity.The results show that work motivation does not significantly affect employee performance. In contrast, both leadership and communication style have a positive and significant partial effect on employee job satisfaction. Furthermore, work motivation, leadership, and communication style have a positive and significant simultaneous effect on employee performance at the Buleleng Regency Tourism Office.